Effect of an herbal supplement on quality of life in participants with insomnia: A randomized placebo controlled cross-over pilot trial - Prachi Singh; Isabella Griffith; Makayla Tanksley; Robbie A. Beyl; Frank Greenway (PLoS ONE, 2026)
Background Insomnia is a common sleep disorder linked to poor quality of life. Patients with insomnia frequently rely on herbal supplements to improve sleep and quality of life; however, most supplements do not undergo rigorous testing to determine their effectiveness. The primary objective of the pilot trial was to test the effectiveness of the herbal supplement on sleep and quality of life. Methods In a double-blind, randomized, placebo-controlled, crossover pilot trial, participants were assigned study drinks consisting of the herbal supplement containing extracts from chicory and green tea or placebo for 7 days. This was followed by a crossover to the other arm after 2 weeks of a washout period. Participants were healthy individuals of the age of 50 years or more with insomnia. Study measures included subjective assessments of sleep, daytime sleepiness, fatigue, and quality of life via questionnaires. Habitual sleep patterns and sleep architecture were objectively evaluated by a 7-day accelerometry and polysomnography. Results Ten participants (9 women; age 59 ± 6 y; BMI 30 ± 10 kg/m 2 ) with insomnia severity index of 21 ± 4 and wake after sleep onset (WASO) of 75 ± 33 min were enrolled in the study. The impact of placebo and supplement was different for measures related to daytime sleepiness and physical fatigue but not quality of life. No within and between treatment differences were observed for any objective measures of habitual sleep patterns or sleep architecture. Within group analysis showed improvement in subjective sleep quality, daytime sleepiness, and general fatigue after 7-day consumption of the placebo drink, but not after consumption of herbal supplement. There were no adverse events related to study participation. Conclusion Compared to placebo drink, daily consumption of the herbal supplement for 7 days did not improve any aspect of quality of life or sleep in our pilot study participants with insomnia. Well controlled clinical trials are needed to confirm the claims related to supplements.